2020
DOI: 10.1021/acsanm.0c02086
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Derived Ceria-Supported Ni–Co Alloy Nanocatalysts for Hydrogenation of Nitroarenes

Abstract: Metal−organic framework (MOF)-templated strategy is an effective route to fabricate nanocatalysts for heterogeneous catalytic reactions. In this work, a coordinationevaporation-calcination (CEC) strategy was developed to synthesize a ceria (CeO 2 )-supported Ni−Co alloy catalyst (termed Ni− Co/CeO 2 -CEC) from a quaternary MOF (named as Ni−Co−Zn− Ce−H 2 salen) designed by metalloligand strategy. The Ni−Co− Zn−Ce−H 2 salen and its cross-bridging Zn 2+ ions simultaneously acted as self-sacrificing templates beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…20 Compared with NiCo-HT, the above peaks for the NiCo-SG, NiCo-PC, NiCo-WT, and NiCo-ST catalysts shift to the lower angle region, which are between the diffraction peaks of the metallic Ni and the metallic Co, belonging to the (111), (200), and (220) planes of Ni-Co alloy. 21 Somorjai found that when the atomic radii of Ni and Co are very close, this promoted the formation of Ni-Co alloys. 22 To verify the presence of the Ni-Co alloy in the NiCo composite catalysts, we calculated the interplanar distances In addition, the interplanar distance of 0.2030 nm for the (111) peak for the NiCo-HT catalyst is the same as the interplanar distance for the (111) peak for metallic Ni, indicating that no Ni-Co alloy was formed in the NiCo-HT catalyst.…”
Section: Xrd Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Compared with NiCo-HT, the above peaks for the NiCo-SG, NiCo-PC, NiCo-WT, and NiCo-ST catalysts shift to the lower angle region, which are between the diffraction peaks of the metallic Ni and the metallic Co, belonging to the (111), (200), and (220) planes of Ni-Co alloy. 21 Somorjai found that when the atomic radii of Ni and Co are very close, this promoted the formation of Ni-Co alloys. 22 To verify the presence of the Ni-Co alloy in the NiCo composite catalysts, we calculated the interplanar distances In addition, the interplanar distance of 0.2030 nm for the (111) peak for the NiCo-HT catalyst is the same as the interplanar distance for the (111) peak for metallic Ni, indicating that no Ni-Co alloy was formed in the NiCo-HT catalyst.…”
Section: Xrd Characterizationmentioning
confidence: 99%
“…For Ni–Co bimetallic catalysts, it has been reported that they might demonstrate greater activity and reproducibility via the formation of Ni–Co alloy. 4 For example, Wang et al prepared a series of bifunctional catalysts for Ni–Co alloy coupled with an oxophilic NbO x support for the HDO reaction of lignin-derived phenolics to generate cycloalkanes. The complete conversion of guaiacol was achieved by Ni–Co alloy and oxygen vacancy, and the selectivity of cycloalkane reached 98.9%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recyclability of catalysts is a significant criterion in the heterogeneous reactions. [60][61][62] Therefore, the reusability of FeS x -Fe 2 O 3 @CN-8 catalyst was investigated in Figure 6. The magnetic property of FeS x -Fe 2 O 3 @CN-8 was measured by the Quantum Design SQUID MPMS-XL7 magnetometer.…”
Section: Reusability Of Fes X -Fe 2 O 3 @Cn-8 Catalystmentioning
confidence: 99%
“…Due to the synergistic effect between the active metal and the second metal, enhanced hydrogenation performance is achieved. For example, CuNi alloy nanoparticles (NPs) exhibited good performance for catalytic transfer hydrogenation of nitroarene using ethylene glycol as the hydrogen donor, 32 while ceria-supported NiCo alloy catalysts derived from the metal-organic framework 33 demonstrated an aniline yield of 87.9% under 150 °C and 2 MPa of H 2 . NiCu/C@SiO 2 -800 34 catalysts could smoothly transform various substituted nitroaromatics to the corresponding aromatic amines at 120 °C and 2.0 MPa of H 2 , and CoN x -Co y Zn s @NPC catalysts 35 achieved high activity and selectivity, affording almost complete conversions and >98% selectivity in water/methanol mixed solvents.…”
Section: Introductionmentioning
confidence: 99%